The Magus as Renaissance Man - Borchardt, Frank L. (The sixteenth century journal, 1990)
The facts of the history of magic in early modern Europe are well known. Two observations are, however, not commonly made and appear here to contribute to the discussion of Renaissance magic: (1) the unusual instance of direct contacts which bind French, German, and Italian intellectuals around the year 1500 into a tight network and (2) the widespread, virtually universal disappointment in magic expressed by the magicians themselves. This feature of the intellectual biographies of the magi became a literary commonplace, for example, in Shakespeare and Goethe, and should henceforth be understood as an intrinsic feature of the myth of the magus.